2009
DOI: 10.1016/j.bbmt.2008.12.502
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Abnormal Findings Detected by Comprehensive Clinical Evaluation at 1 Year after Allogeneic Hematopoietic Cell Transplantation

Abstract: Consensus guidelines recommend a number of screening examinations for survivors following allogeneic hematopoietic cell transplantation (HCT) but the frequency of detecting abnormal findings is unknown. We reviewed medical records of 118 patients who had comprehensive, standardized evaluations at one year after allogeneic HCT at Fred Hutchinson Cancer Research Center/Seattle Cancer Care Alliance. Abnormal findings were common, including moderate-severe pulmonary dysfunction (16%), fasting hyperlipidemia (56%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, data from our study and others have shown that although these cardiovascular risk factors develop frequently after HCT, especially following allogeneic transplant, it appears that many HCT survivors do not receive specific treatment for these conditions(32;35;36). Our reliance on medication status to define cardiovascular risk factors in this study likely underestimates the true prevalence of these conditions.…”
Section: Discussionmentioning
confidence: 52%
“…However, data from our study and others have shown that although these cardiovascular risk factors develop frequently after HCT, especially following allogeneic transplant, it appears that many HCT survivors do not receive specific treatment for these conditions(32;35;36). Our reliance on medication status to define cardiovascular risk factors in this study likely underestimates the true prevalence of these conditions.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies, conducted largely in allogeneic HCT recipients, have reported wide-ranging estimates for prevalence of hypertension (15%-70%), 9,12,13,16 diabetes (7%-30%), 12,16 and dyslipidemia (16%-56%), 10,14,16 due, in part, to a variety of definitions used for CVRFs and varying lengths of follow-up of the study cohorts. In the current study, we used a conservative approach to defining CVRFs, therefore a condition had to be present for Ͼ 6 months and persist for Ͼ 1 year after HCT, highlighting the magnitude of disease burden that persists long after the immediate post-HCT period.…”
Section: Discussionmentioning
confidence: 99%
“…Although recurrence of primary disease remains the leading cause of mortality after HCT, 3,28,29 nonmalignant late effects such as CVD contribute increasingly with longer follow-up, 4-6 a problem that can be compounded by the high prevalence of CVRFs in HCT survivors, as demonstrated in the current study. Studies to date have been limited by relatively short follow-up after HCT, 12-14 reliance on questionnaire-based self-reported outcomes, 9 lack of comparison with the general population, 11,12,14 and lack of information regarding the contribution of CVRFs in the development of CVD in patients previously exposed to cardiotoxic agents such as anthracyclines and chest radiation. [15][16][17] The current study overcomes these limitations by comprehensively evaluating the risk of CVRFs and their modifying effect on subsequent development of CVD in a large cohort of HCT survivors with 11 700 person-years of followup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Estimates of dyslipidemia in different cohorts who survived at least one year after allogeneic HSCT range from 8.9% in a Canadian group 6 to 56% of patients in a United States cohort, 71% of whom remained on immunosuppressive therapy (IST). 13 Taskinen et al reported that hypertriglyceridemia was present in 39% of a small group of 23 survivors of childhood allogeneic HSCT in Finland, excluding patients on active steroid therapy. 14 This was compared with the prevalence of 8% of patients in a group of 13 survivors of acute lymphoblastic leukemia who were treated with chemotherapy but no HSCT.…”
Section: Dyslipidemia and Other Cardiovascular Risk Factors In Hsct Pmentioning
confidence: 99%